From powders to bulk metallic glass composites - Lisa Krämer (Nature Portfolio, 2017)
Abstract One way to adjust the properties of materials is by changing its microstructure. This concept is not easily applicable on bulk metallic glasses (BMGs), because they do not consist of grains or different phases and so their microstructure is very homogeneous. One obvious way to integrate inhomogeneities is to produce bulk metallic glass composites (BMGCs). Here we show how to generate BMGCs via high-pressure torsion (HPT) starting from powders (amorphous Zr-MG and crystalline Cu). Using this approach, the composition can be varied and by changing the applied shear strains, the refinement of the microstructure is adjustable. This process permits to produce amorphous/crystalline composites where the scale of the phases can be varied from the micro- to the nanometer regime. Even mixing of the two phases and the generation of new metallic glasses can be achieved. The refinement of microstructure increases the hardness and a hardness higher than the initial BMG can be obtained.